Hypoperfusion Intensity Ratio Is Correlated With the Risk of Parenchymal Hematoma After Endovascular Stroke Treatment. Issue 1 (23rd November 2022) - Winkelmeier, Laurens; Heit, Jeremy J.; Adusumilli, Gautam; Geest, Vincent; Christensen, Soren; Kniep, Helge; van Horn, Noel; Steffen, Paul; Bechstein, Matthias; Sporns, Peter; Lansberg, Maarten G.; Albers, Gregory W.; et al.
Abstract : Background: Parenchymal hematoma (PH) is a major complication after endovascular treatment (EVT) for ischemic stroke. The hypoperfusion intensity ratio (HIR) represents a perfusion parameter reflecting arterial collateralization and cerebral microperfusion in ischemic brain tissue. We hypothesized that HIR correlates with the risk of PH after EVT. Methods: Retrospective multicenter cohort study of patients with large vessel occlusion who underwent EVT between 2013 and 2021 at one of the 2 comprehensive stroke centers (University Medical Center Hamburg-Eppendorf, Germany and Stanford University School of Medicine, CA). HIR was automatically calculated on computed tomography perfusion studies as the ratio of brain volume with time-to-max (Tmax) delay >10 s over volume with Tmax >6 s. Reperfusion hemorrhages were assessed according to the Heidelberg Bleeding Classification. Primary outcome was PH occurrence (PH+) or absence (PH−) on follow-up imaging. Secondary outcome was good clinical outcome defined as a 90-day modified Rankin Scale score of 0 to 2. Results: A total of 624 patients met the inclusion criteria. We observed PH in 91 (14.6%) patients after EVT. PH+ patients had higher HIR on admission compared with PH− patients (median, 0.6 versus 0.4; P <0.001). In multivariable regression, higher admission blood glucose (adjusted odds ratio [aOR], 1.08 [95% CI, 1.04–1.13]; P <0.001), extensive baseline infarct defined as Alberta Stroke Program Early CT Score ≤5 (aOR, 2.48 [1.37–4.42]; P =0.002), and higher HIR (aOR, 1.22 [1.09–1.38]; P <0.001) were independent determinants of PH after EVT. Both higher HIR (aOR, 0.83 [0.75–0.92]; P <0.001) and PH on follow-up imaging (aOR, 0.39 [0.18–0.80]; P =0.013) were independently associated with lower odds of achieving good clinical outcome. Conclusions: Poorer (higher) HIR on admission perfusion imaging was strongly associated with PH occurrence after EVT. HIR as a surrogate for cerebral microperfusion might reflect tissue vulnerability for reperfusion hemorrhages. This automated and quickly available perfusion parameter might help to assess the need for intensive medical care after EVT.